Impact of Vimentin on Regulation of Cell Signaling and Matrix Remodeling - Ostrowska-Podhorodecka, Zofia; Ding, Isabel; Norouzi, Masoud; McCulloch, Christopher A. (Frontiers in Cell and Developmental Biology, 2022)
Vimentin expression contributes to cellular mechanoprotection and is a widely recognized marker of fibroblasts and of epithelial-mesenchymal transition. But it is not understood how vimentin affects signaling that controls cell migration and extracellular matrix (ECM) remodeling. Recent data indicate that vimentin controls collagen deposition and ECM structure by regulating contractile force application to the ECM and through post-transcriptional regulation of ECM related genes. Binding of cells to the ECM promotes the association of vimentin with cytoplasmic domains of adhesion receptors such as integrins. After initial adhesion, cell-generated, myosin-dependent forces and signals that impact vimentin structure can affect cell migration. Post-translational modifications of vimentin determine its adaptor functions, including binding to cell adhesion proteins like paxillin and talin. Accordingly, vimentin regulates the growth, maturation and adhesive strength of integrin-dependent adhesions, which enables cells to tune their attachment to collagen, regulate the formation of cell extensions and control cell migration through connective tissues. Thus, vimentin tunes signaling cascades that regulate cell migration and ECM remodeling. Here we consider how specific properties of vimentin serve to control cell attachment to the underlying ECM and to regulate mesenchymal cell migration and remodeling of the ECM by resident fibroblasts.